Education in The Period of Adult Development and Its Implications on Education - Ari Mawarni; Muhammad Halim Munandar; Kasinyo Harto; Ermis Suryana (Jayapangus Press, 2022)
This research looks at education in adult development and how it affects education. This study is motivated by the rapid advancement of science, technology, and communication at this time, which necessitates the development and improvement of human quality as a solution to face the current of modernization; thus, an educational process is required that can play an active role in following changes and developments that exist both now and in the future. Recognize that adulthood is a time when you have reached a mature and complete view of life, which can be achieved through consistent decision-making. However, it frequently appears when people fail to recognize the significance of adulthood and middle age. The goal of this study was to examine and analyze education during the adult development period, as well as its surprise in education. This study employs an approach approach in data processing through literature analysis, particularly literature descriptions. Helping people face life's problems objectively, assisting adults with problem-solving skills, assisting people in changing social circumstances, and assisting people in acquiring or skills required to complete their life needs are all realizations of adult education practices that are frequently overlooked.